Jackknife Model Averaging of the Current Account Determinants - Urošević, Branko; Nedeljković, Milan; Zildžović, Emir (Panoeconomicus, 2012)
This paper investigates the short to medium-term empirical relationships between the current account balances and a broad set of macroeconomic determinants in Serbia and selected CEE countries. Using novel model averaging techniques we focus the analysis to individual country’s data only. The results suggest that the model tracks the current account movements over the past decade quite well and captures its relative volatility. Signs and magnitudes of different coefficients indicate significant heterogeneity among countries providing empirical support for the country-level analysis. Key words: Current account, Model averaging, Transition countries. JEL: F32.